2021
DOI: 10.3390/jcm10040638
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Hypoechoic Micronodules in Patients with Hashimoto′s Thyroiditis Increases the Risk of an Alarming Cytological Outcome

Abstract: The aim of the study was to identify a possible relation between various ultrasonographic (US) appearances of Hashimoto′s thyroiditis (HT) and the risk of obtaining an alarming cytology of coexisting nodules. The study included 557 patients with HT, who had been referred for fine needle aspiration biopsy (FNA). We divided US patterns of HT (UP-HT) into eight groups: (a) Hypoechoic (compared to submandibular glands), homogeneous/fine echotexture; (b) hypoechoic, heterogeneous/coarse echotexture; (c) marked hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Experience is necessary to avoid the interpretation of ill-defined pseudonodules as true nodules. Our team is fully aware of that danger due to our previous studies on the relation between FNA outcomes in patients with HT and different ultrasonographic images of thyroid parenchyma, including variants with pseudonodules [ 29 ]. All systems analyzed in our study regard irregular margins as suspicious.…”
Section: Discussionmentioning
confidence: 99%
“…Experience is necessary to avoid the interpretation of ill-defined pseudonodules as true nodules. Our team is fully aware of that danger due to our previous studies on the relation between FNA outcomes in patients with HT and different ultrasonographic images of thyroid parenchyma, including variants with pseudonodules [ 29 ]. All systems analyzed in our study regard irregular margins as suspicious.…”
Section: Discussionmentioning
confidence: 99%
“…That refers particularly to category III. Our previous analysis indicated that patients with HT cytological outcomes of category III constituted as much as 15.6% of all FNA and 17.9% of diagnostic FNA [17], over twice as much as in the general population examined at our center-with or without HT (6.4% of diagnostic FNA) [18]. The suspicious cytology may be more common in HT patients because of postulated higher incidence of papillary carcinoma (PTC) in that cohort [15,19].…”
Section: Introductionmentioning
confidence: 84%
“…The clinical diagnosis of HT was based on clinical symptoms, levels of anti-thyroid antibodies, serum concentrations of thyroid-stimulating hormone and thyroid hormones, ultrasound (US) examination, as well as microscopic examination. A detailed description of ultrasonographic features which we considered characteristic of HT was shown in our previous study [17]. We consider the following cytological image as typical of HT: inflammatory cells (lymphocytes, plasmacytes predominating in the smears) and thyroid follicular cells (usually scattered or clustered in small groups) showing anisocytosis and frequently oxyphilic metaplasia.…”
Section: Patientsmentioning
confidence: 99%
“…Of the few studies that assessed the relationship between anti-Tg titer and hypoechogenicity, none has found any such association [17,18]. It is still arguable whether all patients with autoimmune thyroid diseases are at increased risk for nodules and thyroid cancer or whether there are certain thyroid characteristics that increase this risk [19]. In our study, mean serum TSH, anti-Tg, and anti-TPO titers were signi cantly higher in patients with macronodules than those with micronodules and subjects without nodules.…”
Section: Discussionmentioning
confidence: 99%